Pulp Treatment Management of Primary Molars in Patient with Fanconi Anemia: ACase Report - Nosrat Nourbakhsh; Mona Esmaeli (Isfahan University of Medical Sciences, 2022)
Fanconianemia is a rare autosomal recessive disease that is associated with chromosome failure and impaired DNA repair. The aim of this study was to report a case of Fanconi anemia and to manage the treatment of deciduous tooth pulp and its periodic clinical follow-up.Case Report:The patient is a six-year-old boy with a definitive diagnosis of Fanconi anemia who referred to the Pediatric Dentistry Department of Isfahan University of Medical Sciences with a complaint of deciduous tooth decay and pain on chewingfood. The patient had prominent signs like short stature, hirsutism, pigmented face, contiguous eyebrows, coarse hair, protruding forehead, flat nose bridge and large ears.Conclusion:Despite the low platelet count, it was possible to treat two teeth simultaneously in one session and no particular problem has been observed until the case is reported. It is recommended that taking into account the general health of the patient is very important in providing a treatment plan